Analisis Konten Iklan Citra (1980-2010) Bagi Standardisasi Kecantikan Indonesia: Kacamata Feminis Marxist - Tika Tazkya Nurdyawati; Avis Kafabih; Anggit Akbar Anugrah (Connected: Jurnal Ilmu Komunikasi, 2021)
A product will be promoted will be promoted with persuasive advertising in order to achieve high sales. However, advertising content can cause other social effect from the packaging of the message delivered. Citra as a beauty product from the Unilever company has the jargon of “beautiful skin typical of Indonesia”. This journal is intended to analyze the effect of Citra’s advertising content on Indonesian beauty standards. The method used is secondary qualitative with the help oh Publish or Perish, VosViewer, and Atlas.ti woftware for code classification. Referring to the semiotic framework proposed by Charles Sanders Pearce, the analysis in this article uses a Feminist-Marxist perspective. The results of the study found that Citra products use an adaptive strategy with the times and use the word “beautiful” as a new construction that encourages women’s false awareness to buy their products.